Shifting Quaternary migration patterns in the Bahamian archipelago: Evidence from the Zamia pumila complex at the northern limits of the Caribbean island biodiversity hotspot. Issue 5 (17th May 2017) - Salas‐Leiva, Dayana E.; Meerow, Alan W.; Calonje, Michael; Francisco‐Ortega, Javier; Griffith, M. Patrick; Nakamura, Kyoko; Sánchez, Vanessa; Knowles, Lindy; Knowles, David
Abstract : PREMISE OF THE STUDY: The Bahamas archipelago is formed by young, tectonically stable carbonate banks that harbor direct geological evidence of global ice‐volume changes. We sought to detect signatures of major changes on gene flow patterns and reconstruct the phylogeographic history of the monophyletic Zamia pumila complex across the Bahamas. METHODS: Nuclear molecular markers with both high and low mutation rates were used to capture two different time scale signatures and test several gene flow and demographic hypotheses. KEY RESULTS: Single‐copy nuclear genes unveiled apparent ancestral admixture on Andros, suggesting a significant role of this island as main hub of diversity of the archipelago. We detected demographic and spatial expansion of the Zamia pumila complex on both paleo‐provinces around the Piacenzian (Pliocene)/Gelasian (Pleistocene). Populations evidenced signatures of different migration models that have occurred at two different times. Populations on Long Island ( Z. lucayana ) may either represent a secondary colonization of the Bahamas by Zamia or a rapid and early‐divergence event of at least one population on the Bahamas. CONCLUSIONS: Despite changes in migration patterns with global climate, expected heterozygosity with both marker systems remains within the range reported for cycads, but with significant levels of increased inbreeding detected by the microsatellites. This finding is likely associated with reduced gene flow between and within paleo‐provinces, accompanied by genetic drift, as rising seas enforced isolation. Our study highlights the importance of the maintenance of the predominant direction of genetic exchange and the role of overseas dispersion among the islands during climate oscillations.